Application of Case-Based Wordwall Media to Improve Primary School Students' Critical Thinking Abilities: Penerapan Media Wordwall Berbasis Kasus Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Agustin, Nurul; Rudianto, Rahmat; Resti Fauziah, Ria (Madrosatuna: Journal of Islamic Elementary School, 2024)
Learning at SDN Jatikalang II Krian-Sidoarjo class V on the subject of energy transfer between living things, student learning outcomes are very low, low learning outcomes are influenced by sources of teaching materials that do not attract students' attention and the teacher's lack of creativity in developing teaching materials. Lack of knowledge regarding the use of learning media, especially website-based learning media, to improve student learning outcomes, what needs to be improved is how the teacher's role is in processing the class, how students respond in participating in learning activities in completing assignments with the type of problem solving presented in wordwall media. With the background of the problem above, the aim is to improve students' critical thinking through the application of case-based wordwall media. This research is a type of classroom action research (PTK) that goes through four stages, namely planning, action, observation and reflection, with data collection techniques of observation, interviews, tests and questionnaires. The results of research on student activities in cycle I obtained a percentage of 79% and increased in cycle II by 90%, the results of student activities obtained a percentage of 80% and increased in cycle II by 95%. These results greatly influenced student learning outcomes with the achievement in cycle I of 80% increasing in cycle II to 95%, while the results of the questionnaire in the form of student responses in applying wordwall media to learning activities were obtained at 92.5%. From these results it can be concluded that the application of wordwall media can be applied for problem solving and improving students' critical thinking.